Strategi Badan Pendapatan Daerah (BAPENDA) dalam Penerapan Peraturan Daerah Kota Pekanbaru Nomor 10 Tahun 2011 Tentang Pajak Sarang Burung Walet - Sri Wahyuni; Febri Yuliani (Journal of Social and Policy Issues, 2021)
This research is motivated by the seriousness of the Pekanbaru City government to reorganize the potential for local taxes, one of which is an effort to increase Regional Original Income through the swiftlet nest tax sector. The target to be achieved in the implementation of the swallow nest tax is to increase swallow nest tax revenue in Pekanbaru City by carrying out the strategies that have been established in the Organizational Strategic Plan. This study aims to describe and analyze the strategy of the Regional Revenue Agency |in the application of Pekanbaru City Regulation Number 10 of 2011 concerning Swallow's Nest Tax. The method used in this study is qualitative, data collection techniques using interviews, observation, and documentation. This study uses Koteen's Theory which uses four types of strategies, namely: Organizational Strategy, Program Strategy, Resource Support Strategy, and Institutional Strategy. Based on the results of the study, it can be concluded that the strategy of the Regional Revenue Agency in the application of Pekanbaru City Regulation Number 10 of 2011 concerning Swallow's Nest Tax has not run optimally. The inhibiting factor for the Strategy of the Regional Revenue Agency in the Implementation of the Pekanbaru City Regulation Number 10 of 2011 concerning the Swallow's Nest Tax, namely, the payment provisions that have not been maximized, and the program implemented has not been maximized. This has an influence on the Strategy of the Regional Revenue Agency in the Implementation of Pekanbaru City Regulation Number 10 of 2011 concerning Swallow's Nest Tax